Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru - Maryodona, Maryodona (Journal of Innovation in Teaching and Instructional Media, 2021)
This article aims to describe the influence of the Principal's Leadership on Teacher Performance in SD Negeri 116 OKU. This quantitative research involved 13 teachers in SD Negeri 116 OKU as research subjects. The data are obtained using a questionnaire and then analyzed using descriptive statistics. The results showed that there was an increase in teacher performance by 15%, while other factors had a negative impact. It is proven that school leadership provides benefits to the performance of teachers at SD Negeri 116 OKU.